2013
DOI: 10.3917/mav.064.0121
|View full text |Cite
|
Sign up to set email alerts
|

Identification des mécanismes d'appropriation d'un produit alimentaire en fonction de son degré d'élaboration

Abstract: Brunel Olivier et al., « Identification des mécanismes d'appropriation d'un produit alimentaire en fonction de son degré d'élaboration »,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
(4 reference statements)
0
6
0
6
Order By: Relevance
“…Sur le second volet, l’appropriation repose sur des stratégies dont les formes recoupent la valeur eudémonique telle qu’étudiée dans cette recherche : l’individu augmente son sentiment de contrôle/maîtrise, fait acte de créativité et développe ses connaissances (Brunel et al, 2013 ; Dehling et Vernette, 2019 ; Sartre, 1943).…”
Section: Discussion : Contributions Théoriques Et Implications Managéunclassified
See 1 more Smart Citation
“…Sur le second volet, l’appropriation repose sur des stratégies dont les formes recoupent la valeur eudémonique telle qu’étudiée dans cette recherche : l’individu augmente son sentiment de contrôle/maîtrise, fait acte de créativité et développe ses connaissances (Brunel et al, 2013 ; Dehling et Vernette, 2019 ; Sartre, 1943).…”
Section: Discussion : Contributions Théoriques Et Implications Managéunclassified
“…Si l’on prend le cas d’une pratique domestique, comme celle de la cuisine « fait maison », l’acquisition, petit à petit des fondamentaux permet de profiter davantage de l’activité (De Certeau et al, 1994). Le fait de « faire » permet, par un processus d’adaptation, de minorer les désagréments des premiers pas (comme la présence de grumeaux dans une béchamel) et de laisser plus de place au plaisir, en laissant, par exemple, libre cours à sa créativité (Brunel et al, 2013). L’intensité de la pratique se reflète alors dans la fréquence des actes (plus de plats seront « faits maison »), mais aussi dans la diversité et la technicité des gestes réalisés (les recettes seront plus variées et plus élaborées) (Starke et al, 2015 ; Urban et Ŝčasnỳ, 2016).…”
Section: Modèle Conceptuel De La Relation Entre Intensité De Réalisatunclassified
“…On the second component, appropriation is based on strategies, the forms of which intersect with the eudemonic value as studied in this research: the individual increases his or her sense of control/mastery, acts creatively and develops his or her knowledge (Belk, 1988; Brunel et al, 2013; Dehling and Vernette, 2020; Sartre, 1943).…”
Section: Discussion: Theoretical Contributions and Managerial Implicamentioning
confidence: 99%
“…The complexity of the task and the qualification acquired through experience are associated with a diversity of tasks and the joy of knowing how to do them well (De Certeau et al, 1994). The fact of ‘doing’ makes it possible, through a process of adaptation, to minimize the inconveniences of the first steps (such as the presence of lumps in a sauce) and to leave more room for pleasure, for example, by giving free rein to one’s creativity (Brunel et al, 2013). The intensity of the practice is then reflected in the frequency of the acts (more dishes will be homemade), and also in the diversity and technical nature of the gestures performed (the recipes will become more varied and elaborate) (Starke et al, 2015; Urban and Ŝčasnỳ, 2016).…”
Section: Conceptual Model Of the Relationship Between The Intensity Omentioning
confidence: 99%
“…The re-appropriation process in marketing In marketing, appropriation initially was integrated, under the influence of environmental psychology (Brunel et al, 2012), as a behavioural and psychological process and in reaction to classical behavioural models such as the atmosphere model (Kotler, 1973;Mehrabian and Russell, 1974) that had appeared in retail research. In this stream, appropriation generally gets treated to interpretative approaches (ethnological, life narrative method, semi-structured interviews) but is applied to a wide range of contexts, including retail spaces (Aubert-Gamet, 1996;Bonnin, 2002;Cova, 2001, 2004;Ladwein, 2003;Petr, 2002), retail web sites (Michaud-Trevinal, 2011), food (Brunel and Roux, 2006;Brunel et al, 2009Brunel et al, , 2013, recorded music (Chaney, 2007), second-hand objects (Dehling, 2013), virtual game experiences (Kolenc, 2008), olfactory interactions (Ochs, 2005), and artistic experiences (Carù and Cova, 2003) (see Table II). Among these approaches, two main research streams can be identified.…”
Section: Appropriation In Human and Social Sciencesmentioning
confidence: 99%